Genes targeted by the Hedgehog-signaling pathway can be regulated by Estrogen related receptor β. Issue 1 (December 2015) - Lu, Yuan; Li, Jilong; Cheng, Jianlin; Lubahn, Dennis
Abstract Background Nuclear receptor family member, Estrogen related receptor β, and the Hedgehog signal transduction pathway are both reported to relate to tumorigenesis and induced pluripotent stem cell reprogramming. We hypothesize that Estrogen related receptor β can modulate the Hedgehog signaling pathway and affect Hedgehog driven downstream gene expression. Results We established an estrogen related receptor β-expressing Hedgehog-responsive NIH3T3 cell line by Esrrb transfection, and performed mRNA profiling using RNA-Seq after Hedgehog ligand conditioned medium treatment. Esrrb expression altered 171 genes, while Hedgehog signaling activation alone altered 339 genes. Additionally, estrogen related receptor β expression in combination with Hedgehog signaling activation affects a group of 109 Hedgehog responsive mRNAs, includingHsd11b1, Ogn, Smoc2, Igf1, Pdcd4, Igfbp4, Stmn1, Hp, Hoxd8, Top2a, Tubb4b, Sfrp2, Saa3, Prl2c3 andDpt . Conclusions We conclude that Estrogen related receptor β is capable of interacting with Hh-signaling downstream targets. Our results suggest a new level of regulation of Hedgehog signaling by Estrogen related receptor β, and indicate modulation of Estrogen related receptor β can be a new strategy to regulate various functions driven by the Hedgehog signaling pathway.